Current Trends of Rice Milling Byproducts for Agricultural Applications and Alternative Food Production Systems - Bodie, Aaron R.; Micciche, Andrew C.; Atungulu, Griffiths G.; Rothrock, Michael J.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2019)
Rice is one of the most economically important foods in the world today. The FAO has reported that managing rice processing and the resulting byproducts into more sustainable applications would be attractive for a variety of reasons. Rice processing involves several milling stages to produce edible final products. The milling process is the most important step in rice production because it sets the nutritional, cooking, and sensory qualities of crude rice. As crude rice goes through the milling process, it generates byproducts, such as bran, that have been shown to exhibit beneficial impacts on human and animal nutrition. While several rice byproducts have applications in agriculture, rice bran has probably received the most attention for its functional properties. Rice bran is a mixture of protein, fat, ash, and crude fiber. However, rice bran’s composition is largely dependent on the type of rice and the efficiency of the milling system. Based on studies with mice, rice bran has been shown to elicit prebiotic-like properties by preventing colonization of Salmonella in the gastrointestinal tract. More recently, in vitro incubation studies with chicken cecal contents have demonstrated that certain rice varieties are more inhibitory to Salmonella than others. Some of this may be related to impacts on cecal microbiome and production of certain metabolites. In this review, the byproducts of the milling process, how they are utilized, and potential application for conventional and alternative poultry production systems are discussed.